ChemInform Abstract: Defect Chemistry and Defect Engineering of TiO2‐Based Semiconductors for Solar Energy Conversion. Issue 1 (17th December 2015) - Nowotny, Janusz; Alim, Mohammad Abdul; Bak, Tadeusz; Idris, Mohammad Asri; Ionescu, Mihail; Prince, Kathryn; Sahdan, Mohd Zainizan; Sopian, Kamaruzzaman; Teridi, Mohd Asri Mat; Sigmund, Wolfgang
Abstract: Review: 55 refs.